VARIASI NUKLEOTIDA GEN COI PADA BURUNG SEMPIDAN (GENUS LOPHURA) - Astuti, Dwi; Irham, Mohammad; Ashari, Hidayat (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTGallopheasant birds (Genus Lophura) belonging to Phasianidae family. L. inornata and L.ignita were 2 of 5 species in Indonesia. This study was aimed to determine the genetic variation and diversity of those two bird species based on DNA sequences of COI gene. Total genomic DNA was extracted from blood samples and wet meat from 5 individuals (4 individuals L.inornata hoogerwerfi and 1 individual L. Ignita). Amplification of COI gene by PCR produced a single fragment of about 860 bp. The 785 bp of DNA sequence data from 5 birds were analyzed to determine its genetic variation and diversity, both of at intra and inter-species levels using MEGA 5 software. Genetic distance between individual bird (intraspecific) of L.i. hoogerwerfii ranged from 0.00 to 0.0013 ± 0.0012, whereas between 2 species (L. hoogerwerfii vs L. ignita) ranged from 0.0467 ± 0.0078 to 0.0481 ± 0.0080. Three individuals of L. i. hoogerwerfii have the same DNA sequence haplotype (HLh1) and one individual has one haplotype that was very different from the other 3 individuals (HLh2), so from 4 indi-vidual birds there were only 2 haplotypes with 0.400 ± 0.237 haplotype diversity (Hd) value. Nucleotide substi-tution / differences occured in 4 nucleotide sites (site 320, 711, 738, and 779) and nucleotide diversity (Pi) was 0.00204 ± 0.00121. Between two species (L.i.hoogerwerfii and L. ignita) occured 39 - 404 nucleotide subsitu-tion sites. The average number of codon encoding amino acid was 261 with a value of codon bias was 0.314. The existence of a nucleotide substitution indicated that there were genetic variations in both intraspecies and interspesies levels. Genetic variation and diversity of L.i. hoogerwerfii were low. Information from this re-search is useful for conservation of this bird.Keywords: DNA sequence, COI, genetic variation, Lophura inornata hoogerwerfii, L. ignita.